Sibling Rivalry as a Predictor of Emotional Regulation in Adolescents - Ramayani Habeahan, Elpida; Mirza, Rina; Bangun, Erika Guspita Windari; Bangun, Loide Ibrena Theresia; Marpaung, Winida (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Adolescence is a developmental period characterized by intense emotional changes, making emotional regulation an essential aspect of adolescents’ psychological adjustment. One factor presumed to influence emotional regulation is sibling rivalry. This study aims to examine the relationship between sibling rivalry and emotional regulation among adolescents. The research employed a quantitative correlational design. The sample consisted of 105 students from grades X and XI at Panca Budi Private High School Medan, selected using purposive sampling. Data were collected using the sibling rivalry scale and emotional regulation scale, then analyzed using Pearson Product Moment correlation with IBM SPSS Statistics version 27. The results showed a correlation coefficient of r = -0.788 with p < 0.001 (p < 0.05), indicating a significant negative relationship between sibling rivalry and emotional regulation among adolescents. This means that higher levels of sibling rivalry are associated with lower emotional regulation, and vice versa. These findings suggest that the quality of sibling relationships plays an important role in adolescents’ emotional regulation development and may serve as a basis for family-based interventions to support adolescent emotional well-being.Masa remaja merupakan periode perkembangan yang ditandai dengan perubahan emosional yang intens, sehingga kemampuan regulasi emosi menjadi aspek penting dalam penyesuaian psikologis remaja. Salah satu faktor yang diduga memengaruhi regulasi emosi adalah sibling rivalry. Penelitian ini bertujuan untuk mengetahui hubungan antara sibling rivalry dan regulasi emosi pada remaja. Penelitian menggunakan metode kuantitatif dengan pendekatan korelasional. Sampel penelitian berjumlah 105 siswa kelas X dan XI di SMA Swasta Panca Budi Medan yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui skala sibling rivalry dan skala regulasi emosi, kemudian dianalisis menggunakan korelasi Pearson Product Moment dengan bantuan IBM SPSS Statistics versi 27. Hasil penelitian menunjukkan koefisien korelasi sebesar r = -0,788 dengan nilai p < 0,001 (p < 0,05), yang menunjukkan adanya hubungan negatif yang signifikan antara sibling rivalry dan regulasi emosi pada remaja. Artinya, semakin tinggi sibling rivalry, maka semakin rendah regulasi emosi remaja, dan sebaliknya. Temuan ini menunjukkan bahwa kualitas hubungan antarsaudara memiliki peran penting dalam perkembangan regulasi emosi remaja serta menjadi dasar bagi intervensi keluarga untuk mendukung kesehatan emosional remaja.